Awareness on female contraceptives safety, efficacy and side effects among nursing undergraduates at KIU, Sri Lanka - Razzaag B.A; Mizna F; Shaamila H; Saffath H; Tanika Gayani Kanchana (Intelektual Pustaka Media Utama, 2022)
Nurses being an integral part of the health care system should have sufficient awareness on contraceptives since unplanned pregnancies have rapidly emerged as a social issue that severely deteriorates the quality of life of parents and children. The objective of the study was to assess the awareness on contraceptive safety, efficacy and side effects among nursing undergraduates at KAATSU International University (KIU). A descriptive cross-sectional study was conducted among 362 undergraduate nurses studying at KIU, higher education institute of Sri Lanka using convenient sampling method. The data was collected using pre-tested questionnaire and data was analyzed using descriptive statistic and Pearson Chi square test. The questionnaire consisted with four parts; demographic variables, safety, efficacy and side effects related questions. Out of total, 74.6% of the participants had an average knowledge regarding different type of female contraceptives and 74.5% had average knowledge regarding major side effects of female contraceptives. When the knowledge regarding efficacy of different contraceptive methods was found to be only 37% related to female condom. Overall findings of the study reflect that majority of the nurses had average knowledge regarding safety and major side effects of female contraceptive methods and a poor knowledge was identified regarding the efficacy of female contraceptive methods among undergraduate nurses.